Rotating stall inception in fans of low hub-tip ratio - Soundranayagam, M. (Cranfield University, 1991)
An investigation was carried out to study the process of rotating stall inception in a low hub-tip ratio fan. Such fans are expected, based on an elementary analysis, to stall from the root. However, experimental evidence had led to the belief that the fans stalled from the tip. The effects of streamtube contraction were first studied and this was followed by an experimental investigation on an isolated rotor, with successive build modifications to increase the likelihood of rotating stall inception occurring at the root. A computer based streamline curvature method was used to study the effects of streamtube contraction and streamtube diffusion that commonly occur when a fan is operated at flows below its' design flow rate. The results indicated a reduced expectation for the root to stall first when compared to a simple 2-D flow analysis. Experimental measurements were then carried out to determine how the experimental local characteristics differed from the predicted characteristics. It was apparent that real fluid effects tended to steepen the root characteristic, thus enhancing the stability of the root. The tip characteristics tended to droop and become less stable. The enhancement of the root stability was also seen in the profiles of deviation angle. The axial Velocity contours at the rotor exit supported the conclusion that the root stability enhancement was caused by "centrifuging". To determine the actual radial location of rotating stall inception, an array of hot wires was used to record events during the inception transient. Inception was first detectable at the tip. This tip stalling behaviour persisted for all the build modifications. Measurements of unsteady pressure were also made to study the movement of the overall operating point since it was felt that this could continuously alternate between a pair of closely spaced characteristics. The results indicated that the fan operated along a unique characteristic. The overall conclusion was that a low hub-tip ratio fan shows a strong reluctance to stall at the root due to "centrifuging" of the blade boundary layer. The inception process appears to be dominated by events in the tip region.